BELAJAR BAHASA INGGRIS DENGAN FLASHCARD UNTUK ANAK USIA DINI - varia virdania virdaus (Universitas Narotama, 2022)
AbstractThis study aims to show that there are various methods of learning English in early childhood using flashcard media. Not only it can add new vocabulary but also it can improve speaking and listening skills. According to Sandra Fox, apart from generally adding vocabulary, here are some interesting methods of using flashcards, namely Cahin Mini-Dialogue, Guessing Mimes, Guessing Mimes behind Back, TPR, Describing Activities, and Exchanging Information. Some of the methods of using the flashcards mentioned above are very interesting, they make students (early childhood) enjoy learning English. Keywords: flashcard, learning method, English